1989
DOI: 10.1084/jem.170.2.613
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 3 and interleukin 6 synergistically promote the proliferation and differentiation of malignant plasma cell precursors in multiple myeloma.

Abstract: PBMC from 11 patients with multiple myeloma (MM) were cultured in vitro in presence of IL-3 and IL-6. After 3 d, actively proliferating immunoblast-like B cells (20-62%) were apparent. After 6 d, a population of morphologically evident plasma cells was observed (30-50%) that expressed, in each individual case, the same light and heavy chain produced by bone marrow malignant plasma cells. We conclude that in MM the malignant plasma cell precursors are circulating and their growth and terminal differentiation ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
2
2

Year Published

1991
1991
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(60 citation statements)
references
References 23 publications
3
53
2
2
Order By: Relevance
“…Even though there are several in vitro evidences of IL-3 activity on lymphoid cells [18][19][20], we did not observe acute or chronic effects during seven days of IL-3 treatment on the subpopulations of B and T lymphocytes and natural killer (NK) circulation cells. There are two possibilities (not mutually exclusive) that may explain this apparent discrepancy between in vivo and in vitro observations: 1) IL-3 only acts upon immature progenitors, and as such several cell generations (lasting more than the seven-day duration of our studies) are needed to ensure that the lymphopoietic stimulus is evident in the peripheral blood parameters.…”
contrasting
confidence: 91%
“…Even though there are several in vitro evidences of IL-3 activity on lymphoid cells [18][19][20], we did not observe acute or chronic effects during seven days of IL-3 treatment on the subpopulations of B and T lymphocytes and natural killer (NK) circulation cells. There are two possibilities (not mutually exclusive) that may explain this apparent discrepancy between in vivo and in vitro observations: 1) IL-3 only acts upon immature progenitors, and as such several cell generations (lasting more than the seven-day duration of our studies) are needed to ensure that the lymphopoietic stimulus is evident in the peripheral blood parameters.…”
contrasting
confidence: 91%
“…2,3 Among these cytokines, IL-6 is considered as the major growth and survival factor for myeloma cells. [4][5][6] The findings that IL-6-gene deficient mice fail to develop plasma cell tumors, 7 that some of the MM cell lines are IL-6-dependent, and that IL-6 is a proliferative signal for primary MM explants 8,9 led to the hypothesis that IL-6 is an essential growth and survival factor for multiple myeloma (MM).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Furthermore, it has been reported that cytokines induce the differentiation of peripheral blood mononuclear cells obtained from patients with MM into plasma cells. 8,9 The number and phenotype of these B cellrelated cells, as well as their role in the malignant process are still a matter of debate. 7,10 Further resolution of these questions is necessary as a basis for the development of new treatment strategies, since despite treatment intensification most patients ultimately relapse.…”
mentioning
confidence: 99%